The Role of Intervention Incentives in Improving HIV/Aids prevention outcomes in Kyetume Heath Center IV - Emmanuel Davis Kigudde (Uganda Christian University, 2024)
The purpose of the study was to examine the Role of Intervention Incentives in Improving HIV/Aids Prevention Outcomes at Kyetume Health Center IV. The specific objects of the study were to; examine the role of motivation in improving HIV/Aids prevention outcomes, examine the role of behavioral reinforcement in improving HIV/Aids prevention outcomes and examine the role of increased participation in HIV Testing Services (HTS) in improving HIV/Aids prevention outcomes. The study revealed that most respondents are more likely to get tested for HIV as a result of the interventions promoting testing services and HIV-positive individuals are more likely to be linked to care and treatment services following diagnosis because of the interventions in place. The study revealed that the positive perceptions of incentives enhance intrinsic motivation to participate in HIV/AIDS prevention activities. Generally, the study revealed that females contribute more numbers of the respondents compared to the male indicating that most of the patients at Kyetume Health Center IV are female and therefore female are more eligible to receive HIV Testing Services at the health center as compared to the male. The study recommends that the management of Kyetume Health Center IV should integrate its health services within the community systems such that the people actively and primarily participate in the give health services. Conclusively, the study has helped develop managerial recommendations of integrating the health services with the community systems so as to actively influence and involve the people.
Undergraduate research